A multifunctional metal organic sol and its application
By using multifunctional metal organic sol as a protective layer and conductive adhesive in zinc-iodine batteries, the problems of zinc dendrites growth, low conductivity and multi-iodide shuttle are solved, and the high performance and long life of zinc-iodine batteries are achieved.
Patent Information
- Application Number
- CN202411274543.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Zinc-iodine batteries have problems such as short circuits caused by zinc dendrites, low conductivity of iodine cathode and capacity attenuation caused by polyiodide shuttle effect, which affects their performance and life.
Using multifunctional metal organic sol as the protective layer of zinc metal negative electrode and the conductive binder of iodine positive electrode, the combination of sodium alginate, acrylamide, gallium indium alloy and nanosilver particles can achieve uniform transportation of zinc ions and capture of polyiodide, inhibiting zinc dendrites growth and polyiodide shuttle.
Effectively inhibit the growth of zinc dendrites, improve the uniform deposition of zinc ions, reduce the production of gas inside the battery, improve the conductivity of the iodine positive electrode, extend the cycle life of the zinc-iodine battery and improve its electrochemical performance.
Smart Images

Figure CN119092649B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry, and in particular to a multifunctional metal organic sol and application thereof. Background Art
[0002] Lithium-ion batteries are one of the most widely used energy storage devices, but there are huge bottlenecks in their further application. On the one hand, the scarcity of lithium resources and the large consumption of lithium elements have limited the total production capacity of lithium batteries, and the high cost of battery raw materials has kept the price of batteries high; on the other hand, the electrolyte and battery materials are very toxic. Once leaked, they will not only pollute the environment but also harm the human body, and make the battery production conditions extremely harsh; in addition, the increasingly prominent short-circuit and spontaneous combustion of electric vehicle batteries has also cast a shadow on the development of lithium-ion batteries. In this context, it is of great significance to seek new energy storage batteries with lower costs and higher safety.
[0003] In recent years, zinc-iodine batteries, which use zinc metal as the negative electrode and iodine as the positive electrode, have become the focus of researchers. First, zinc metal is naturally abundant, low in price, non-toxic, and has a large theoretical capacity (820 mAh g -1 、5855mAh cm -3 ), low redox potential (-0.762Vvs SHE), and aqueous zinc-ion batteries have a more convenient preparation process, can be directly carried out in the air, and the battery uses an aqueous electrolyte, which is safer and can avoid accidents such as battery explosion. In addition, iodine reserves are abundant and low in price, and the iodine positive electrode has a high theoretical specific capacity (211mAh g -1 ), so zinc-iodine batteries are considered to be highly promising energy storage devices. However, the uneven zinc deposition at the zinc negative electrode easily causes the growth of zinc dendrites, which leads to battery short circuit, and the iodine conductivity in the iodine positive electrode is low, and the conversion kinetics are slow, resulting in low battery coulombic efficiency. In addition, the shuttle effect of multiple iodides can cause the battery capacity to decay sharply, seriously affecting the performance of zinc-iodine batteries.
[0004] In order to solve the many problems of zinc-iodine batteries, researchers have proposed a series of modification measures, including electrolyte optimization, zinc negative electrode protective coating, development of functional binders and other strategies; Professor Lai Feili of the University of Leuven in Belgium and others [Adv.Energy Mater.2023,13,2203790.] constructed a sulfonate-rich ion exchange layer on the surface of the zinc metal negative electrode to regulate the transport of zinc ions at the zinc / electrolyte interface, thereby inhibiting the growth of zinc dendrites, but its inhibitory effect on the shuttling of polyiodides was relatively general, resulting in the failure to significantly extend the cycle life of the zinc-iodine battery; Professor Wu Xinglong et al. of Northeast Normal University [J.Am.Chem.Soc.2024,146,10,6628–6637.] first tried to solve the problems existing in zinc-iodine batteries from the perspective of binders. They creatively used chitosan as a binder for the iodine positive electrode and used the affinity of chitosan polar groups with polyiodides to inhibit the shuttling of polyiodides. However, due to ignoring the problems such as zinc dendrites existing in the zinc metal negative electrode, the zinc-iodine battery failed to have a long cycle life.
[0005] From the above research results, it can be seen that constructing a coating on the surface of the zinc metal negative electrode and developing a functional binder can extend the life of the zinc-iodine battery to a certain extent. However, in order to significantly extend the life of the zinc-iodine battery, it is necessary to utilize the synergistic effect of the zinc negative electrode protective coating and the functional binder to effectively improve the performance of the battery. Summary of the invention
[0006] The purpose of the present invention is to overcome one of the problems existing in the above-mentioned prior art and provide a multifunctional metal organic sol for uniformly transporting ions and capturing polyiodides. The multifunctional metal organic sol for uniformly transporting ions and capturing polyiodides can be used as a zinc metal negative electrode protective layer to prepare a high-performance zinc negative electrode, realize uniform transportation of zinc ions, promote uniform deposition of zinc ions, effectively inhibit the growth of zinc dendrites, and reduce the generation of gas inside the battery by inhibiting the hydrogen evolution reaction to avoid battery bulging; it can also be used as a conductive binder in the positive electrode to prepare a high-performance iodine positive electrode, utilize the affinity of polar groups such as amide groups with polyiodides to capture polyiodides, inhibit the shuttling of polyiodides, and also have a certain conductivity, alleviate the problem of relatively low iodine conductivity in the iodine positive electrode, thereby realizing a long life cycle of the zinc-iodine battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a multifunctional metal organic sol, which comprises the following preparation raw materials: water, sodium alginate, acrylamide, an initiator, a gallium-indium alloy and nano silver particles.
[0009] The multifunctional metal organic sol of the present invention can polymerize into a film on the surface of a zinc metal negative electrode to obtain a high-performance zinc metal negative electrode, realize efficient transportation and uniform deposition of zinc ions, inhibit the growth of zinc dendrites, and reduce the generation of gas inside the battery by inhibiting the hydrogen evolution reaction; it can also utilize the affinity of polar groups such as amide groups and polyiodides to capture polyiodides and inhibit their shuttling to obtain a high-performance iodine positive electrode, and the sol has a certain electrical conductivity, which effectively improves the problem of low iodine conductivity.
[0010] Preferably, the mass ratio of sodium alginate to acrylamide is 1:1 to 1:20; further preferably, the mass ratio of sodium alginate to acrylamide is 1:5 to 1:15.
[0011] Preferably, the mass of the initiator is 0.1% to 2% of the mass of acrylamide; further preferably, the mass of the initiator is 0.5% to 1% of the mass of acrylamide.
[0012] Preferably, the initiator includes at least one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0013] Preferably, the mass ratio of the sodium alginate to the nano-silver particles is 5:1 to 1:5; further preferably, the mass ratio of the sodium alginate to the nano-silver particles is 3:1 to 1:2.
[0014] Preferably, the mass ratio of the gallium-indium alloy to the nano-silver particles is 2:1 to 1:3.
[0015] The second aspect of the present invention provides a method for preparing the multifunctional metal organic sol, comprising the following steps: mixing water, sodium alginate, acrylamide and an initiator for a first stirring, then adding a gallium-indium alloy for a second stirring, and then adding nanosilver particles for a third stirring to obtain the multifunctional metal organic sol.
[0016] Preferably, the second stirring speed is 500 r / min to 2000 r / min, and the third stirring speed is 500 r / min to 2000 r / min.
[0017] The third aspect of the present invention provides the use of the multifunctional metal organic sol in the preparation of zinc negative electrode of zinc iodine battery.
[0018] A fourth aspect of the present invention provides a zinc negative electrode for a zinc-iodine battery, wherein the zinc negative electrode structure comprises a zinc metal sheet and the multifunctional metal organic sol loaded on the surface of the zinc metal sheet.
[0019] Preferably, the loading amount of the multifunctional metal organic sol on the surface of the zinc negative electrode is 0.01-0.5 ml / cm 2 .
[0020] In the present invention, the method for preparing the zinc negative electrode of the zinc-iodine battery comprises the following steps: coating the multifunctional metal organic sol on the surface of the zinc metal sheet, and then drying. Preferably, the coating speed is 10-30 mm / s; the drying temperature is 50-70°C, and the drying time is 3-5 hours.
[0021] The fifth aspect of the present invention provides the use of the multifunctional metal organic sol in the preparation of the iodine positive electrode of the zinc-iodine battery. When used in the preparation of the iodine positive electrode, the functional metal organic sol is used as a conductive binder.
[0022] The sixth aspect of the present invention provides a method for preparing an iodine positive electrode for a zinc-iodine battery, comprising the following steps: mixing iodine powder, activated carbon, conductive carbon black and the multifunctional metal organic sol, adding water, stirring to obtain a slurry, then coating the slurry on graphite paper, and drying to obtain an iodine positive electrode.
[0023] Preferably, the drying temperature is 50-70° C., and the drying time is 3-5 hours.
[0024] Preferably, the mass ratio of the iodine powder, activated carbon, conductive carbon black and multifunctional metal organic sol is (3-5):(3-5):(0.9-1.1):1.
[0025] A seventh aspect of the present invention provides an iodine positive electrode for a zinc-iodine battery, which is prepared by the preparation method.
[0026] An eighth aspect of the present invention provides a zinc-iodine battery, wherein the negative electrode of the zinc-iodine battery is the zinc negative electrode, and the positive electrode of the zinc-iodine battery is the iodine positive electrode.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention prepares a multifunctional metal organic sol that uniformly transports ions and captures polyiodides by a stirring and mixing method. Different from the conventional preparation method of large-scale ultrasound, the preparation method of the present invention is simple and the preparation process is relatively mature. The obtained sol components are uniform and have the prospect of large-scale preparation.
[0029] (2) The present invention controls the amount of added sodium alginate, acrylamide, gallium-indium alloy, and nano-silver particles to obtain a multifunctional metal organic sol with different component ratios for uniform ion transport and capture of polyiodides. The multifunctional metal organic sol can be used as a protective layer for the zinc metal negative electrode to prepare a high-performance zinc metal negative electrode, and can also be used as a conductive binder for the iodine positive electrode to prepare a high-performance iodine positive electrode. The synergistic effect of the multifunctional metal organic sol for uniform ion transport and capture of polyiodides on the positive and negative electrodes realizes a high-performance zinc-iodine battery.
[0030] (3) The high-performance zinc metal negative electrode used in the present invention is conducive to the rapid transportation of zinc ions and realizes the uniform deposition of zinc ions, thereby inhibiting the growth of zinc dendrites. It can also inhibit the occurrence of hydrogen evolution reaction, reduce the generation of gas during battery cycling, and avoid battery bulging.
[0031] (4) The high-performance iodine positive electrode used in the present invention can inhibit the shuttling of polyiodides through the affinity of polar groups such as amide groups to polyiodides, avoid the rapid loss of battery capacity, and also have a certain effect on improving the conductivity of iodine. Through the synergistic effect of the high-performance negative electrode and the high-performance positive electrode, a zinc-iodine battery with high capacity and long cycle life is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a functional diagram of a zinc-iodine battery;
[0033] Figure 2 is a scanning electron microscope photograph of the high-performance zinc negative electrode prepared in Example 2;
[0034] Figure 3 is a scanning electron microscope photograph of the zinc metal negative electrode of Comparative Example 1;
[0035] Figure 4 is a contact angle photograph of the high-performance zinc negative electrode prepared in Example 2;
[0036] Figure 5 This is a contact angle photograph of the zinc metal negative electrode of Comparative Example 1;
[0037] Figure 6 The symmetrical battery assembled with the high-performance zinc negative electrode prepared in Example 2 was operated at a current density of 0.5 mA cm -2 , with a deposition / stripping capacity of 0.5 mAh cm -2 The cycle curve of
[0038] Figure 7 This is a scanning electron microscope photograph of the high-performance zinc negative electrode prepared in Example 2 after 50 cycles;
[0039] Figure 8 The symmetrical battery assembled with the zinc metal negative electrode of Example 1 was operated at a current density of 0.5 mA cm -2 , the deposition capacity density is 0.5 mAh cm -2 The cycle curve of
[0040] Fig. 9 This is a scanning electron microscope photograph of the zinc metal negative electrode of Comparative Example 1 after 50 cycles;
[0041] Fig.10 is the Tafel curve spectrum of the high-performance zinc negative electrode prepared in Example 2;
[0042] Fig.11 is the Tafel curve spectrum of the zinc metal negative electrode of Comparative Example 1;
[0043] Fig.12 It is a linear sweep voltammetric curve of the high performance zinc negative electrode prepared in Example 2;
[0044] Fig.13 is a linear sweep voltammetry curve of the zinc metal negative electrode of Comparative Example 1;
[0045] Fig.14 It is a full battery cycle diagram of a pair of a high-performance iodine positive electrode prepared in Example 3 and a high-performance zinc negative electrode prepared in Example 2;
[0046] Fig.15 This is a full battery cycle diagram of a pair of a conventional iodine positive electrode prepared in Comparative Example 2 and a high-performance zinc negative electrode prepared in Example 2;
[0047] Fig.16 It is a full battery charge and discharge curve diagram of a pair of a high-performance iodine positive electrode prepared in Example 3 and a high-performance zinc negative electrode prepared in Example 2;
[0048] Fig.17 This is a full battery charge and discharge curve diagram of a pair of a conventional iodine positive electrode prepared in comparative example 2 and a high-performance zinc negative electrode prepared in example 2. DETAILED DESCRIPTION
[0049] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0050] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0051] Example 1
[0052] 0.25 g of sodium alginate powder, 3 g of acrylamide powder and 0.0225 g of ammonium persulfate powder were added to 10 mL of deionized water, and stirred overnight on a magnetic stirrer at room temperature to obtain a mixture 1. 0.125 g of gallium-indium alloy was added to mixture 1, and the mixture was placed in a planetary mixer, and the speed was set to 1500 r / min for planetary mixing for 5 minutes, and the gallium-indium alloy was dispersed into fine droplets to obtain a mixture 2. 0.25 g of nanosilver particles was added to mixture 2, and the mixture was placed in a planetary mixer, and the speed was set to 1500 r / min for planetary mixing for 5 minutes to obtain a mixture 3 with uniform component distribution, i.e., a multifunctional metal organic sol.
[0053] Example 2
[0054] Cutting 100*100*0.1mm -3 A zinc metal sheet of standard specifications was wiped dry with alcohol and placed on a coating machine, 1 mL of the multifunctional metal organic sol prepared in Example 1 was dripped on the zinc metal sheet, and the coating speed was set to 20 mm / s. Then, the zinc metal sheet was placed in an oven at 60°C for 4 hours of thermal polymerization to obtain a high-performance zinc metal sheet with a protective layer. A metal disc with a diameter of 12 mm was obtained using a button battery slicer.
[0055] The electrode of this embodiment is composed of a zinc metal negative electrode and a coated protective layer. Figure 2 The scanning electron microscope image shows that a dense protective layer has formed on the surface of zinc metal. Figure 4 From the contact angle photograph, it can be seen that the high-performance zinc negative electrode prepared in this embodiment has a small contact angle, showing good hydrophilicity, and the wettability of the electrode surface is improved, which is beneficial to reduce the charge transfer resistance, can accelerate the migration rate of zinc ions, and make the zinc ion deposition / stripping more uniform.
[0056] Example 3
[0057] Iodine, activated carbon, conductive carbon black and the multifunctional metal organic sol prepared in Example 1 were weighed in a mass ratio of 4:4:1:1. First, 0.3 g of iodine was put into an agate mortar and fully ground to obtain iodine powder, which was transferred to a glass bottle. Then, 0.3 g of activated carbon, 0.075 g of conductive carbon and 0.075 g of the multifunctional metal organic sol prepared in Example 1 were added in sequence. Then, 5 mL of deionized water was added and stirred to obtain a slurry with uniform components. The slurry was then coated on a graphite paper with a diameter of 12 mm and a thickness of 0.1 mm, and placed in a 60°C oven for 4 h to obtain an active material loading of 1 mg cm -2 ~2mg cm -2 High performance iodine positive electrode.
[0058] Example 4
[0059] 1 g of sodium alginate powder, 3 g of acrylamide powder and 0.03 g of ammonium persulfate powder were added to 10 mL of deionized water, and stirred overnight on a magnetic stirrer at room temperature to obtain a mixture 1. 1 g of gallium-indium alloy was added to mixture 1, and the mixture was placed in a planetary mixer, and the speed was set to 1500 r / min for planetary mixing for 5 minutes, and the gallium-indium alloy was dispersed into fine droplets to obtain a mixture 2. 0.5 g of nanosilver particles were added to mixture 2, and the mixture was placed in a planetary mixer, and the speed was set to 1500 r / min for planetary mixing for 5 minutes to obtain a mixture 3 with uniform component distribution, i.e., a multifunctional metal organic sol.
[0060] Example 5
[0061] Cutting 100*100*0.1mm -3 A zinc metal sheet of standard specifications was wiped dry with alcohol and placed on a coating machine, 1 mL of the multifunctional metal organic sol prepared in Example 4 was dripped on the zinc metal sheet, and the coating speed was set to 20 mm / s. Then the zinc metal sheet was placed in an oven at 60°C for 4 hours of thermal polymerization to obtain a high-performance zinc metal sheet with a protective layer. A metal disc with a diameter of 12 mm was obtained using a button battery slicer.
[0062] Example 6
[0063] Iodine, activated carbon, conductive carbon black and the multifunctional metal organic sol prepared in Example 4 were weighed in a mass ratio of 4:4:1:1. First, 0.3 g of iodine was put into an agate mortar and fully ground to obtain iodine powder, which was transferred to a glass bottle. Then, 0.3 g of activated carbon, 0.075 g of conductive carbon and 0.075 g of the multifunctional metal organic sol prepared in Example 4 were added in sequence. Then, 5 mL of deionized water was added and stirred to obtain a slurry with uniform components. The slurry was then coated on a graphite paper with a diameter of 12 mm and a thickness of 0.1 mm, and placed in a 60°C oven for 4 h to obtain a slurry with an active material loading of 1 mg cm -2 ~2mg cm -2 High performance iodine positive electrode.
[0064] Example 7
[0065] The high-performance zinc anode prepared in Example 2 was assembled into a symmetrical battery using 2 mol L -1 Zinc sulfate aqueous solution was used as the electrolyte, Whatman glass fiber membrane was used as the diaphragm, and the test conditions were a current density of 0.5 mA cm -2 and a deposition / dissolution capacity of 0.5 mAh cm -2 When the test results are Figure 6 As shown in Figure 2, it can be seen that it has excellent cycle stability. The scanning electron microscope photo of the electrode surface after 50 cycles is shown in Figure 2. Figure 7 As shown, it can be seen that the zinc deposition is generally uniform.
[0066] Comparative Example 1
[0067] The pure zinc metal sheet was wiped dry with alcohol as the zinc metal negative electrode of Comparative Example 1. The scanning electron microscope photo is shown in Figure 3 The pure zinc metal sheet was assembled into a symmetrical battery, using a 2 mol / L zinc sulfate aqueous solution as the electrolyte, a Whatman glass fiber membrane as the separator, and the test condition was a current density of 0.5 mA cm -2 and a deposition / dissolution capacity of 0.5 mA cm -2When the test results are Figure 8 As shown in Figure 2, it can be seen that the battery life formed by assembling a pure zinc metal negative electrode is short. The scanning electron microscope photo of the electrode surface after 50 cycles is shown in Figure 2. Fig. 9 As shown, the results show that zinc metal deposition is uneven, which easily forms zinc dendrites and causes battery short circuit.
[0068] Comparative Example 2
[0069] Iodine, activated carbon, conductive carbon black and carboxymethyl cellulose were weighed in a mass ratio of 4:4:1:1. First, 0.3 g of iodine was put into an agate mortar and fully ground to obtain iodine powder, which was transferred to a glass bottle. Then, 0.3 g of activated carbon, 0.075 g of conductive carbon, and 0.075 g of carboxymethyl cellulose were added in sequence. Then, 5 mL of deionized water was added and stirred to obtain a slurry with uniform components. The slurry was then coated on a graphite paper with a diameter of 12 mm and a thickness of 0.1 mm, and dried in an oven at 60 °C for 4 h to obtain a slurry with an active material loading of 1 mg cm -2 ~2mg cm -2 The conventional iodine positive electrode.
[0070] Example 8
[0071] The high performance zinc negative electrode prepared in Example 2 and the pure zinc metal prepared in Comparative Example 1 were used as test objects, and the Tafel curve and linear sweep voltammetry curve were tested using an electrochemical workstation. Fig.10 , Fig.11 It can be seen that the high-performance zinc negative electrode prepared in Example 2 has a more positive corrosion potential, that is, has higher corrosion resistance; Fig.12 , Fig.13 It can be seen that the high-performance zinc negative electrode prepared in Example 2 has a more negative hydrogen evolution potential, that is, it can better inhibit the occurrence of hydrogen evolution reaction.
[0072] Example 9
[0073] The high-performance iodine positive electrode prepared in Example 3 and the conventional iodine positive electrode prepared in Comparative Example 2 were used as positive electrodes, the high-performance zinc negative electrode prepared in Example 2 was used as negative electrode, a 2 mol / L zinc sulfate aqueous solution was used as an aqueous electrolyte, and a Whatman glass fiber membrane was used as a separator. A full battery was assembled to conduct an electrochemical performance test. Fig.14 , Fig.15 , Fig.16 , Fig.17 As shown, it can be seen that the zinc-iodine battery formed by assembling the high-performance iodine positive electrode prepared in Example 3 and the high-performance zinc negative electrode prepared in Example 2 has more stable capacity retention and longer cycle life.
[0074] The high-performance iodine positive electrode prepared in Example 3 and the conventional iodine positive electrode prepared in Comparative Example 2 were used as positive electrodes, and the high-performance zinc negative electrode prepared in Example 2 was used as negative electrode to assemble a full battery, and the electrochemical performance test was carried out. The results are as follows:
[0075] Table 1
[0076]
[0077] As can be seen from the above table, the lateral comparison data of Example 3 and Comparative Example 2 proves that the capacity retention capacity and cycle life of the zinc-iodine battery formed by assembling a high-performance iodine positive electrode prepared by the multifunctional metal organic sol prepared by the present invention as a binder are higher than those of the zinc-iodine battery assembled by a conventional iodine positive electrode prepared by a conventional binder, that is, the electrochemical performance of the zinc-iodine battery is significantly improved.
[0078] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. Application of a multifunctional metal organic sol in the preparation of zinc negative electrode and / or iodine positive electrode of zinc-iodine battery, characterized in that: The multifunctional metal organic sol comprises the following raw materials: water, sodium alginate, acrylamide, an initiator, a gallium-indium alloy and nano-silver particles; the preparation method of the multifunctional metal organic sol comprises the following steps: mixing water, sodium alginate, acrylamide and an initiator for a first stirring, then adding the gallium-indium alloy for a second stirring, and then adding the nano-silver particles for a third stirring to obtain the multifunctional metal organic sol.
2. The use according to claim 1, characterized in that: The mass ratio of sodium alginate to acrylamide is 1:1-1:20; the mass of the initiator is 0.1%-2% of the mass of acrylamide; the mass ratio of sodium alginate to nano-silver particles is 5:1-1:5; the mass ratio of the gallium-indium alloy to nano-silver particles is 2:1-1:
3.
3. The use according to claim 1, characterized in that: The zinc negative electrode structure comprises a zinc metal sheet and a multifunctional metal organic sol loaded on the surface of the zinc metal sheet.
4. The use according to claim 1, characterized in that: The preparation method of the iodine positive electrode comprises the following steps: mixing iodine powder, activated carbon, conductive carbon black and multifunctional metal organic sol, adding water, stirring to obtain slurry, then coating the slurry on graphite paper, and drying to obtain the iodine positive electrode.
5. The use according to claim 4, characterized in that: The mass ratio of the iodine powder, activated carbon, conductive carbon black and multifunctional metal organic sol is (3-5):(3-5):(0.9-1.1):1.
Citation Information
Patent Citations
Zinc ion battery liquid metal composite negative electrode and preparation method and application thereof
CN111916744A
Preparation and application of zinc-iodine battery positive electrode carrier with ship-in-bottle structure
CN115411269A
Aqueous zinc-iodine battery positive electrode material based on amphiphilic molecules, preparation method of aqueous zinc-iodine battery positive electrode material and battery
CN117650230A